Post‐Crosslinkable Blends: Reactions Between a Linear Poly(hydroxyl‐amino ether) and a Diepoxy - Constantin, François (2004)
A thermoplastic poly(hydroxyl‐amino ether) polymer (BLOX) was blended with a diglycidyl ether of bisphenol A monomer (DGEBA). This system may be used as a crosslinkable thermoplastic. It means that it may be processed in an extruder like a classic thermoplastic, and cured by etherification reactions initiated by tertiary amine groups of the BLOX in a second step, to produce a material with good mechanical properties. In order to understand and quantify the etherification reactions occurring at high temperature (135 °C), between epoxy groups of the diepoxy and hydroxyl groups of the thermoplastic, a model system was studied based on DGEBA in excess and ethanolamine. In the model system the rate of the etherification reaction was well described by a second‐order kinetic equation. The specific rate constants and the epoxy conversion at the gel were related to the polarity of the reactive medium. The polyetherification occurring in the DGEBA‐BLOX system could also be fitted with a second‐order kinetics. A significant increase in the reaction rate was observed when using high BLOX concentrations.